Microencapsulation of Carotene Extracts from Neurospora sp. Spores With Protein Based Encapsulant Using Spray Drying Method. - Pahlevi, Yusra Widya; Estiasih, Teti; Saparianti, Ella (Jurnal Teknologi Pertanian, 2008)
Neurospora sp. produces intracellular carotenoids pigment stored in its conidia, makes orange color appearance. Carotene was extracted from spores using acetone-hexane (2:1) as solvent and virgin coconut oil (VCO) was used to facilitate dilution of carotene extract. The objective of this research was to obtain the appropriate type of encapsulant and proportion of core material to obtain good quality carotene microcapsules for food industry and health purposes.This research was conducted by randomized block design with 2 factors. The first factor was type of encapsulant (soy proteinate isolate, sodium caseinate, and whey protein isolate) and the second factor was proportion of carotene extract (20, 30 and 40% w/w on encapsulant basis).The result of this study showed that microcapsule with sodium caseinate as encapsulant and 30% proportion of carotene extract had the highest microencapsulation efficiency, total carotenes, and carotenes retention values. Whereas microcapsule with soy proteinate isolate and 20% proportion of carotene extract had the highest water content and microcapsule yield. Microcapsule with soy proteinate isolate had the highest red and yellow value, and sodium caseinate had the highest lightness value. The most stable microcapsule during storage at temperature of 70oC was microcapsule with sodium caseinate as encapsulant and 20% proportion of carotene extracts.Key words: carotene, Neurospora sp., protein based encapsulant, microencapsulation